Highly reliable and efficient encoding systems for hexadecimal polypeptide-based data storage - Yubin Ren; Yi Zhang; Yawei Liu; Qinglin Wu; Hong-Gang Hu; Jingjing Li; Chunhai Fan; Dong Chen; Kai Liu; Hongjie Zhang (Fundamental Research, 2023)
Polypeptides consisting of amino acid (AA) sequences are suitable for high-density information storage. However, the lack of suitable encoding systems, which accommodate the characteristics of polypeptide synthesis, storage and sequencing, impedes the application of polypeptides for large-scale digital data storage. To address this, two reliable and highly efficient encoding systems, i.e. RaptorQ-Arithmetic-Base64-Shuffle-RS (RABSR) and RaptorQ-Arithmetic-Huffman-Rotary-Shuffle-RS (RAHRSR) systems, are developed for polypeptide data storage. The two encoding systems realized the advantages of compressing data, correcting errors of AA chain loss, correcting errors within AA chains, eliminating homopolymers, and pseudo-randomized encrypting. The coding efficiency without arithmetic compression and error correction of audios, pictures and texts by the RABSR system was 3.20, 3.12 and 3.53 Bits/AA, respectively. While that using the RAHRSR system reached 4.89, 4.80 and 6.84 Bits/AA, respectively. When implemented with redundancy for error correction and arithmetic compression to reduce redundancy, the coding efficiency of audios, pictures and texts by the RABSR system was 4.43, 4.36 and 5.22 Bits/AA, respectively. This efficiency further increased to 7.24, 7.11 and 9.82 Bits/AA by the RAHRSR system, respectively. Therefore, the developed hexadecimal polypeptide-based systems may provide a new scenario for highly reliable and highly efficient data storage.